2020
DOI: 10.1039/c9ra08829f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological activity study of the retro-isomer of RhTx against TRPV1

Abstract: TRPV1 is a ligand-gated ion channel and plays an important role in detecting noxious heat and pain. A new TRPV1 antagonist RL-RhTx was discovered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The trends of CD spectra of different folded peptides were basically identical, which was consistent with previous studies (Figure 4B). 34 The CD spectrum of linear peptide 1 was significantly different from those of folded RhTx, which indicates that disulfide bonds were necessary for maintaining the structure of RhTx.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The trends of CD spectra of different folded peptides were basically identical, which was consistent with previous studies (Figure 4B). 34 The CD spectrum of linear peptide 1 was significantly different from those of folded RhTx, which indicates that disulfide bonds were necessary for maintaining the structure of RhTx.…”
Section: Resultsmentioning
confidence: 99%
“…Using CHO cells overexpressing TRPV1, the agonistic effects of The time courses of TRPV1 currents showed that the folded peptides could induce the similar trend of the TRPV1 currents, which were comparable with the previous studies (Figure 5A-I). 34 Besides, linear peptide 1 could not activate TRPV1 channel, indicating the necessity of disulfide bonds (Figure 5J). There was no significant difference between the normalized currents induced by the folded peptides (Figure 5K).…”
Section: The Patch-clamp Activity Evaluationmentioning
confidence: 99%
See 2 more Smart Citations